A National Survey of Outpatient Platelet Transfusion Practice. Issue 6 (26th August 2022) - O'Brien, Kerry; Bakhtary, Sara; Benson, Kaaron; Stephens, Laura; Lu, Wen
Abstract: Objectives: Platelets are a limited resource frequently subject to inventory shortages. It benefits all to transfuse judiciously, according to evidence-based guidelines. Several organizations have published recommendations for platelet transfusions, but none specifically focused on outpatients. The Clinical Hemotherapy subsection of the Association for the Advancement of Blood & Biotherapies (AABB) Transfusion Medicine Subsection Coordinating Committee conducted a survey targeting outpatient transfusions to understand current practice in the United States. Methods: To determine use of platelets in the outpatient setting, a survey was developed, piloted, validated, and distributed by email to 735 AABB members. Frequencies were calculated and free-text comments categorized. Results: A total of 317 responses were received (43% response rate) from 44 states. Half the respondents' institutions have formal outpatient platelet guidelines. Slightly more than half the respondents (51%) with guidelines used a threshold of less than 10, 000/µL when transfusing stable, afebrile outpatients, with 29% using less than 20, 000/µL. Fewer than half (45%) monitored outpatient platelet use by prospective and retrospective audits, with the next-largest group (25%) using retrospective audits only. Conclusions: Approximately half the respondents had outpatient guidelines, and half used a threshold of less than 10, 000/µL when transfusing platelets to stable outpatients. Greater adoption of this threshold and monitoring may improve the nation's platelet inventory.